Pelatihan Dasar Teknik Rudimen/Basic Stiking Pada Ekstrakurikuler Drum Band di SMP Pembangunan LAB UNP - Wildan Fikri (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
UNP LAB Development Middle School carries out various extracurricular activities, including Scouting, PMR, Paskibra, Football, Basketball, Painting, Dance and Drum Band. Of the several extracurricular activities at UNP LAB Development Middle School which are included in the field of musical arts, namely Drum Band .Basically, Rudiment is basic training for drummers. Rudiment training includes a variety of movements and patterns designed to build strength, accuracy and speed of the hands, as well as improve coordination between the two hands. The method in this research is action research. Action research is an activity or corrective action that is planned, implemented and evaluated systematically so that its validity and reliability reach research level. Action research is a process that includes a cycle of action, which is based on reflection, feedback, evidence and evaluation of previous actions and the current situation. Basic training in rudiment/basic stiking techniques in drum band extracurriculars at UNP DEVELOPMENT SMP as a whole has been proven to be effective. in various forms of percussion playing patterns and help improve the playing skills of junior high school drum band participants UNP LAB DEVELOPMENT. With rudiment training it can help make drum band playing easier. Rudiment training has been proven to have a positive impact on percussion playing procedures, by applying the rudiment method to every percussion game of course the Participants will certainly find it easy to understand percussion playing patterns and can save practice time more efficiently. Apart from that, implementing rudimentary training can reduce the energy expended by UNP LAB DEVELOPMENT SMP drum band participants in playing percussion.